2022
DOI: 10.1177/15563316221101333
|View full text |Cite
|
Sign up to set email alerts
|

Retired Orthopedic Surgeons’ Reflections on Their Lives and Careers: A Cross-Sectional Study

Abstract: Background: Retired surgeons often have limited opportunities to disseminate their wisdom and expertise in a structured manner to their younger colleagues. In addition, when asked to reflect on their personal and professional lives, many physicians say they wish they had done something differently. The extent to which this is true of retired orthopedic surgeons is not known. Purpose: We sought to determine the percentage of retired orthopedic surgeons who say that they would like to have changed something in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In a survey of physicians in the University of Toronto Department of Medicine, 89.5% of respondents preferred to retire gradually and not stop work completely 12 . Almost half of orthopedic surgeons in the US worked PT before retiring (Lee et al, 13 2023). A survey of physicians in British Columbia, Canada, revealed that 40% decreased their work activities by at least 10% in the 3 years before retirement 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of physicians in the University of Toronto Department of Medicine, 89.5% of respondents preferred to retire gradually and not stop work completely 12 . Almost half of orthopedic surgeons in the US worked PT before retiring (Lee et al, 13 2023). A survey of physicians in British Columbia, Canada, revealed that 40% decreased their work activities by at least 10% in the 3 years before retirement 7 .…”
Section: Discussionmentioning
confidence: 99%